2016
DOI: 10.1016/j.jaci.2015.10.045
|View full text |Cite
|
Sign up to set email alerts
|

Childhood asthma exacerbations and the Arg16 β2-receptor polymorphism: A meta-analysis stratified by treatment

Abstract: Background The Gly-to-Arg substitution at the 16 position (rs1042713) in the beta 2 adrenoceptor (ADRB2) gene is associated with enhanced down-regulation and uncoupling of beta-2 receptors. Objectives To undertake a meta-analysis to test the hypothesis that there is an interaction between the A allele of rs1042713 (Arg16 amino acid) and long acting beta agonist (LABA) exposure for asthma exacerbations in children. Methods Children with diagnosed asthma were recruited in five populations (BREATHE, GALA II, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 45 publications
0
63
2
1
Order By: Relevance
“…This hypothesis is supported by a recent large meta-analysis of observational studies gathered in Pharmacogenomics in Childhood Asthma Consortium (PiCA). Turner et al performed a meta-analysis of 4226 children and young adults and showed that patients treated with LABA had a 52% increased risk of exacerbations per copy of the Arg16 risk allele (Figure 3) [25]. Remarkably, patients solely treated with ICS did not have an increased risk.…”
Section: Long-acting Beta-2 Agonistsmentioning
confidence: 99%
“…This hypothesis is supported by a recent large meta-analysis of observational studies gathered in Pharmacogenomics in Childhood Asthma Consortium (PiCA). Turner et al performed a meta-analysis of 4226 children and young adults and showed that patients treated with LABA had a 52% increased risk of exacerbations per copy of the Arg16 risk allele (Figure 3) [25]. Remarkably, patients solely treated with ICS did not have an increased risk.…”
Section: Long-acting Beta-2 Agonistsmentioning
confidence: 99%
“…For this reason, pharmacogenetics studies on heterogeneity in response to inhaled β 2 -agonists have mostly focused on ADRB2 . A recent meta-analysis stratified by treatment showed that the use of a long acting β 2 -agonist (LABA), but not an leukotriene receptor antagonist, as an add-on controller is associated with increased risk of AE in children carrying 1 or 2 A alleles at rs1042713 (Arg16 amino acid) in ADRB2 47. In this study, data from 4,226 children of white Northern European and Latino origin was analyzed, and both severe and non-severe AEs were included.…”
Section: Pharmacogeneticsmentioning
confidence: 99%
“…This variant was shown to be associated with poor response to LABA in children . In a recent meta‐analysis of 4226 asthmatic children included in the multi‐ethnic Pharmacogenomics in Childhood Asthma (PiCA) consortium, patients treated with ICS plus LABA showed an increased risk of asthma exacerbations for each copy of the ADRB2 risk allele (OR 1.52, 95%CI 1.17‐1.99; P = 0.002) . These findings suggest that ADRB2 genotype‐guided treatment can improve disease management.…”
Section: Introductionmentioning
confidence: 97%